Tradisi Fiqh dalam Pemikiran Khalid Abu Al-Fadl - Qurrotul Ainiyah (FALASIFA : Jurnal Studi Keislaman, 2016)
This research is descriptive and reflective, with lifting the theme "Tradition Fiqh Thought Khalid Abu al-Fadl", the theme is intended to explore the key ideas of Khalid discourse on contemporary Islamic legal by analyzing one of his main work, Speaking in God's Name: Islamic Law, Authority, and Women.dengan using content analysis approach to examine in depth the ideas Khalid Abu al-Fadl of Islamic law, the results of this study is the ideology of Salafism Khalid Critics argue that Islamic reformism partly responsible for creating credo closed, intolerant, and shallow in understanding the sacred texts of Islam deserves to be taken seriously. Â Keywords: Fiqh, Khalid